Howlett S. Dostoevsky, Demon of Malraux. Review - Alexander N. Taganov (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2020)
The book here reviewed is particularly important in the field of comparative studies dedicated to Dostoevsky and Malraux, since it is the first attempt to generalize and systematize the connections that unite the creative heritage of the two writers. The interest of Howlett’s book lies in the fact that the author considers Malraux from three different points of view: as a reader, literary theorist, and writer; thus, he creates an original biography of the French writer through the prism of the impact of Dostoevsky’s ideas on him and at the same time a study that allows us to understand Dostoevsky’s role in the development of French literature in the 19th and 20th centuries. Trying to define the role of Dostoevsky in Malraux’s creative development, Howlett speaks of a demonic influence of the Russian writer: Dostoevsky predetermined Malraux’s place as a novelist and literary critic and predicted his fate, being at the same time a “guardian demon” and a tempter, constantly encouraging him to ask the cursed questions of existence. Extracting from Malraux’s texts statements about the Russian author and combining them with his own reflections and observations, Howlett seems to continue and realize Malraux’s unfinished plan to write a book about Dostoevsky.